Proportional yields and processing of pork derived from different halothane hyperthermia pig genotypes - Fisher, Peter Philip (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D. Agric.) -- University of Stellenbosch, 1998.